Impact of lithium-ion coordination in GG–DMSO−LiBOB gel polymer electrolytes: A spectroscopic approach using FTIR deconvolution - Rojudi, Z. E.; Tamchek, N.; Shukur, M. F.; Osman, Z.; Singh, P. K.; Noor, I. M. (Elsevier B.V., 2025)
This work investigates the molecular interactions and complexation behaviour within gel polymer electrolytes (GPEs) composed of gellan gum (GG), dimethyl sulfoxide (DMSO), and lithium bis(oxalato)borate (LiBOB), with emphasis on their structural evolution as a function of salt concentration. Fourier-transform infrared (FTIR) spectroscopy, including peak deconvolution was employed to elucidate the coordination mechanisms of Li+ cations with GG functional groups. The FTIR spectra reveal distinct shifts and intensity changes in the hydroxyl (OH), carbonyl (C[dbnd]O), and carboxylate (COO−) vibrational modes, indicating successful complexation between Li+ cations and the oxygen-containing moieties of GG. Deconvoluted spectra further confirm the formation of H–O⋯Li+, C[dbnd]O⋯Li+, and COO−⋯Li+ interactions. The coordination strength and number of free Li+ cations increased with LiBOB content, reaching an optimum at 13.08 wt% (S4 sample). Beyond which ion pair formation became dominant. Quantitative analysis of the free ion and ion pair fractions between 1850 and 1750 cm−1 region supports this conclusion with the S4 sample exhibiting the highest free ion area fraction of 86.51 %. To validate the spectroscopic findings, electrochemical impedance spectroscopy (EIS) was conducted, revealing that the S4 sample also achieved the highest ionic conductivity of (4.76 ± 0.10) mS cm−1 at room temperature. This strong correlation between FTIR and EIS results confirms the critical role of Li+−polymer coordination in governing charge transport. These findings demonstrate the GG−DMSO−LiBOB system as a tunable, sustainable, and high-performance GPE for next-generation electrochemical energy storage devices.